Reproductive Performance and Population Dynamics of Cattle in Rembang District, Central Java Province - Maulana, Rifal; Priyanti, Atien; Aryogi, Aryogi; Atmoko, Bayu Andri; Wibowo, Agus; Andarwati, Siti; Panjono, Panjono (Faculty of Animal Science, Universitas Gadjah Mada, 2024)
Rembang Regency has the fourth largest cattle population in Central Java Province. Cattle farming in Rembang Regency is mostly conducted by farmers and family farmers with 2 to 4 cattle. The objective of this study was to measure the reproductive performance, natural increase (NI), and population dynamics of cattle in Rembang District, Central Java. The study was conducted using a survey method by collecting data from 400 farmers and 1,275 cattle in five subdistricts in Rembang District. The results showed that the reproductive index value of cows was 0.77 head/year, the natural increase (NI) value was 55.06%, and the average growth of cattle in Rembang District from 2017 to 2022 was 2.81% per year. Based on the results of this study, it can be concluded that the reproductive performance is quite good but there are still many cows with poor reproductive performance in the population and based on population dynamics data, it is concluded that many cattle transported out of Rembang Regency.